Delayed dehiscence of modified mechanical Bentall 7 years postsurgery for Takayasu's arteritis. Issue 5 (14th March 2019) - Fatehi Hassanabad, Ali; Dagher, Olina; Jefferson, Hallie L.; Fine, Nowell M.; Kotha, Vamshi; Mosher, Dianne; Appoo, Jehangir J.
Abstract: Following aortic surgery for vasculitis, the incidence and duration of onset of anastomotic breakdown is unclear. A case is presented of a young female patient with Takayasu's arteritis (TA) who was found to have frank dehiscence of a modified Bentall repair 7 years after surgery. The case highlights (i) the lack of normal healing following aortic surgery in TA, and (ii) need to differentiate imaging protocols for patients with defined vasculitis as opposed to degenerative aortic conditions. A recommendation is made for appropriate surveillance imaging modality alternating between computed tomography and magnetic resonance imaging in the often young patient population affected by vasculitis.